(untitled) (Journal of Forensic Medicine & Toxicology, 2017)
Tuberculosis is the prototype of the granulomatous inflammatory diseases, caused by Mycobacterium tuberculosis. Immune reactions are usually involved in the development of granulomas (referred to as a tubercle in this disease) often characterized by the presence of central caseous necrosis, rare in other granulomatous diseases. Although it is uncommon but when exaggerated by some trauma it may account for sudden death.